Quantitation of Vacuolar Sugar Transporter Abundance Changes Using QconCAT Synthtetic Peptides - Pertl-Obermeyer, Heidi; Trentmann, Oliver; Duscha, Kerstin; Neuhaus, H. Ekkehard; Schulze, Waltraud X. (Frontiers in Plant Science, 2016)
Measurements of protein abundance changes are important for biological conclusions on protein-related processes such as activity or complex formation. Proteomic analyses in general are almost routine tasks in many laboratories. However, a precise and quantitative description of (absolute) protein abundance changes requires careful experimental design and high data quality. A vast choice of metabolic labeling and label-free quantitation protocols are available, but the trade-off between quantitative precision and proteome coverage of quantified proteins as well as missing value problems remain. Here, we provide an example of a targeted proteomic approach using artificial standard proteins consisting of concatenated peptides of interest (QconCAT) to specifically quantify abiotic stress-induced abundance changes in low abundant vacuolar transporters. An advantage of this approach lies in the reliable quantitation of a limited set of low-abundant target proteins throughout different conditions. We show that vacuolar ATPase AVP1, sugar transporters of the ERDL (early responsive to dehydration-like) family, and TMT2 (tonoplast monosaccharide transporter 2) are increased in abundance upon salt stress.